Andro-sterility of corn lines and hybrids in Valles Altos of Mexico. - Tadeo, Margarita; Espinosa, Alejandro; Solano, Ana María; Martínez, Rafael (Agronomía Mesoamericana, 2003)
Lines combinations of andro-sterile progenitors were evaluated to find genotypes with restoring capacity during the years 1995 to 1997. Seven lines were defined and verified to restore the male fertility. Also, some hybrids with andro-sterile progenitors of excellent yield (12230 kg/ha) and possibilities of commercial use (UHS95E0123 X P2-1) were located. The male fertility restoring capacity (100%) of the lines P2-1, IA49-1, IA49-2, EHT-29- 1, EHT-49-3 were confirmed in progeny testing. Besides in 1997 and 1998, the isogenic versions were obtained with the third and up to the fourth back-crosses, from the elite lines from UNAM and the PUMAS female hybrids (in commercial use as the PUMA 1157 and PUMA 1075). Also, there is a version of the andro-sterile progenitors from INIFAP, denominated as H-50 and H-48, recommended for the Valles Altos; as well as some lines from CIMMYT, which could favor the seed production of the hybrids that are generated from these materials.